Pengaruh sistem pengendalian internal dan budaya organisasi terhadap kualitas pelayanan publik berkelanjutan - Nunik Lestari Dewi; Yuliana Gunawan; Soddin Mangunsong; Yohana Meiliana (Universitas Kristen Maranatha, 2021)
Founder and central leaders of policymakers and development in the health sector said several obstacles must be addressed in the health service system, one of which is the low level of hospital services in Indonesia. The health service system in Indonesia still needs to be improved by the government, both in terms of equity, regulation, and system integration. To achieve the goals of sustainable health services, it is necessary to implement an integrated system (internal control system) in the hospital. An effective internal control system can anticipate various environmental changes that occur quickly, increase operational effectiveness and efficiency, and anticipate law violations. To improve the quality of sustainable health services, apart from implementing an internal control system, hospitals also need to carry out various innovations to provide changes in the bureaucratic climate. Innovations are carried out based on learning on all processes that have been carried out by the hospital. Therefore, the objective to be achieved in this study is to determine the effect of internal control systems and organizational culture (innovation and learning culture) on the quality of sustainable public services at BLUD RSUD dr. Slamet, Garut Regency. The data was collected using a survey method using a questionnaire. Data were analyzed using multiple regression methods. The results showed no influence on the internal control system on the quality of sustainable public services, but there was an influence of organizational culture on the quality of sustainable public services.